Nursing doctoral students' experiences of the courses and comprehensive examinations in China: a mixed-methods study - Kehan Liu; Chongmei Huang; Honghong Wang; Siyuan Tang; Minhui Liu (BMC, 2024)
Abstract Background Understanding the experiences of doctoral students regarding courses and comprehensive examinations is crucial to enhance the quality of doctoral programs. Scarce information is available on the experiences of nursing doctoral students on the courses and comprehensive examinations in China. The purpose of this study was to understand the nursing doctoral students' experiences on courses and comprehensive examinations of the doctoral program at Xiangya School of Nursing, Central South University, and propose improvements. Design A convergent parallel mixed methods design adhering to EQUATOR guidelines for Good Reporting of a Mixed Methods Study. Methods A total of 20 doctoral students were recruited through purposive sampling in September 2022 from the Xiangya School of Nursing, Central South University. They completed the self-designed questionnaire on demographic data, course, and comprehensive examination evaluations and participated in focus groups. Quantitative data were analyzed using descriptive statistics. Qualitative data were recorded and transcribed for content analysis. Results Regarding course experience, doctoral students preferred in-person lectures (80%) and group discussions (60%) for specialized compulsory courses. They were satisfied with the course novelty (85%), difficulty (75%), and practicality (85%), and half of the students found the credit allocation reasonable. The qualitative findings revealed their preference for appropriate and blended teaching methods, needs for additional interdisciplinary courses, statistics, and inter-school collaborative courses, accessible Nursing Philosophy and Theory courses, and high proportion of compulsory course credits. Regarding comprehensive examination experience, only 20% considered it necessary, and qualitative data revealed that they prefer more distinctive and effective contents; moreover, students were confused about the purpose of comprehensive examinations. The triangulation of quantitative and qualitative data demonstrated relative convergence. Conclusions These findings illustrated nursing doctoral students' experiences on courses and comprehensive examinations and provide suggestions on improving the courses and comprehensive examinations in China and possibly in the world. This study contributes to improving the quality of nursing doctoral programs in China and can serve as valuable guidance for nursing doctoral programs with similar educational environment around the world that are undergoing course and comprehensive examination reform.